1992
DOI: 10.1002/jnr.490330106
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nerve growth factor mRNA regulation by interleukin‐1β in hippocampal cultures: Role of second messengers

Abstract: Cytokines such as interleukin-1, which are found in the brain after trauma, regulate expression of nerve growth factor (NGF) mRNA and protein in hippocampal cultures. We have investigated possible mechanisms by which Il-1 beta regulates NGF in hippocampal cells. The induction of NGF mRNA by Il-1 beta was blocked by a receptor antagonist indicating that this effect is receptor mediated. Il-1 beta elicited a dramatic induction of c-fos mRNA and a slight elevation of c-jun mRNA in a time dependent manner which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 41 publications
6
24
0
Order By: Relevance
“…In RC7 cells NGF synthesishecretion was dose-dependently upregulated by IL-16 as repeatedly described for astrocytes (Carman-Krzan et al, 1991;Friedman et al, 1992;Spranger et al, 1990;Vige et al, 1991;Yoshida and Gage, 1991) with a dose-effect range comparable to that determined by Carman-Krzan et al (1991) for NGF protein and by Vige et al (1991) for NGF mRNA levels in cortical primary astrocytes. In all three systems the half maximal effective concentration (EC,,) was about 1 U/ml and the maximal effective concentration (EC,,,) 3-10 U/ml.…”
Section: Discussionsupporting
confidence: 62%
“…In RC7 cells NGF synthesishecretion was dose-dependently upregulated by IL-16 as repeatedly described for astrocytes (Carman-Krzan et al, 1991;Friedman et al, 1992;Spranger et al, 1990;Vige et al, 1991;Yoshida and Gage, 1991) with a dose-effect range comparable to that determined by Carman-Krzan et al (1991) for NGF protein and by Vige et al (1991) for NGF mRNA levels in cortical primary astrocytes. In all three systems the half maximal effective concentration (EC,,) was about 1 U/ml and the maximal effective concentration (EC,,,) 3-10 U/ml.…”
Section: Discussionsupporting
confidence: 62%
“…However, the pathway mediating IL-1␤ activation of CREB was undefined. Previous studies had shown no activation of cAMP by IL-1␤ in these cells (Friedman et al, 1992), suggesting that this cytokine may activate CREB by a distinct signaling pathway. Ca 2ϩ signaling also can lead to CREB activation; however, fura-2 analysis of IL-1␤-treated hippocampal neurons revealed no change in calcium signaling.…”
Section: Il-1␤ Signaling In Hippocampal Neuronsmentioning
confidence: 59%
“…CREB can be activated by numerous second messengers, including Ca 2ϩ and cAMP, as well as by the ERK and p38 MAPK signaling pathways. In a previous study, we had shown that IL-1 did not elicit any change in cAMP levels in cultures of hippocampal neurons and glia (Friedman et al, 1992). To determine whether calcium signaling mediated CREB phosphorylation in hippocampal neurons, we monitored intracellular calcium by fura-2 imaging.…”
Section: Il-1 Signaling In Hippocampal Neuronsmentioning
confidence: 99%
“…The signaling pathway does not appear to involve cAMP, protein kinase C, phosphatidylinositol turnover, or mobilization of intracellular calcium (16). Activation of c-fos (16), and the presence of an AP-1 site in the NGF promoter (17,18) suggested a potential role for this transcription factor in mediating Il-1 stimulation of NGF.…”
mentioning
confidence: 99%
“…The signaling pathway does not appear to involve cAMP, protein kinase C, phosphatidylinositol turnover, or mobilization of intracellular calcium (16). Activation of c-fos (16), and the presence of an AP-1 site in the NGF promoter (17,18) suggested a potential role for this transcription factor in mediating Il-1 stimulation of NGF. Alternatively, the recent identification of the sphingomyelin pathway, leading ultimately to activation of NFB transcriptional activity by Il-1 and TNF (19,20), suggested that this pathway might mediate actions of Il-1 in astrocytes.…”
mentioning
confidence: 99%